Between Cervantes and Shakespeare: new ways of writing the history of literature (2012)
It is difficult to do justice to this new book by the French historian Roger Chartier, for the very richness of its content, for the funny novel plot in which it inserts its arguments and the result of its searches, for the quality of the information on w